2019
DOI: 10.1016/j.prevetmed.2019.104784
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of farmers’ compliance in implementing recommended cow comfort changes and their effects on lying time, stall and cow cleanliness within smallholder dairy farms in Kenya

Abstract: Our study aimed to evaluate farmers' compliance in implementing recommendations of farmspecific cow comfort changes, and the effects of these changes on lying time, stall cleanliness and cow cleanliness using a randomized controlled trial carried out on 100 smallholder dairy farms in Kenya, with 62 and 11 farms remaining in the intervention and control groups, respectively. recommendations compared to farms that had the female principal farmer receive the recommendations (OR=0.01); 2) farms that had recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…By optimizing the use of the stated breeding criteria for most of the cows receiving sexed semen in this study, conception percentages were likely optimised in this context. Although the descriptive statistics of this study show that the farms and cows in this study are similar to other studies in Kenya (Gitonga, 2010;Kathambi et al, 2019), this study should be replicated in another area with SDFs in Kenya or elsewhere to confirm the generalizability of the results.…”
Section: Reproductive Interventionsupporting
confidence: 73%
See 1 more Smart Citation
“…By optimizing the use of the stated breeding criteria for most of the cows receiving sexed semen in this study, conception percentages were likely optimised in this context. Although the descriptive statistics of this study show that the farms and cows in this study are similar to other studies in Kenya (Gitonga, 2010;Kathambi et al, 2019), this study should be replicated in another area with SDFs in Kenya or elsewhere to confirm the generalizability of the results.…”
Section: Reproductive Interventionsupporting
confidence: 73%
“…Contamination of the control groups was expected in this study because it has been documented elsewhere among smallholder dairy farmers in Kenya (Kathambi et al, 2019;Makau et al, 2018b). There is a strong desire among the farmers to improve their management, the farmers are often quite willing to share what they know with their neighbours, and the farms are small and therefore close together, making communication between farms relatively easy.…”
Section: Study Limitationsmentioning
confidence: 62%
“…This could be due to the type of flooring, the slipperiness of the flooring, the cleanliness of the stall, a lack of bedding material, and a lack of walking or movement area in most dairy farm enterprises (cows were staying in the barn for long hours). A similar finding revealed that the majority of lactating dairy cows in Kenyan smallholder dairy farms were clinically lame, and lameness is a significant economic problem that reduces milk yield (Kathambi, 2018). According to Geenough (2007), lameness is a clinical sign of pain that can be caused by a variety of hoof and leg diseases and disorders.…”
Section: Cow Comfort Assessment Of Dairy Farm Enterprises 3111 Animal...mentioning
confidence: 92%
“…Improving the knowledge of farmers through on-farm training has been reported to be more valuable than the provision of financial support, because it raises both productivity and income (Murshed-E-Jahan and Pemsl, 2011). While different approaches to farmer training have been studied, including the use of mobile phones (Makau et al, 2018), Kathambi et al (2019) reported that identifying specific on-farm inadequacies and providing a participatory role in management modification led to good acceptance, implementation, and overall animal comfort. Therefore, on-farm farmer training targeted at specific management or facility changes can be a sustainable way of knowledge transfer, attitude change, and enhanced practices.…”
Section: Smallholdermentioning
confidence: 99%
“…Though significant research has been done to demonstrate increased milk yield and improved comfort with enhanced management in cows on smallholder dairy farms (Makau et al, 2019b;Kathambi et al, 2019), little is known about the economic effects of improved calf care. The housing environment is second to nutrition when it comes to achieving improved growth, health and welfare (Costa et al, 2019).…”
Section: Smallholdermentioning
confidence: 99%